Minimally invasive approach in endometrial cancer with lower uterine segment involvement in stage ≥ II: A retrospective study. (January 2022) - Perri, Tamar; Levin, Gabriel; Helpman, Limor; Eitan, Ram; Vaknin, Zvi; Lavie, Ofer; Ben Arie, Alon; Amit, Amnon; Levy, Tally; Namazov, Ahmet; Ben Shachar, Inbar; Atlas, Ilan; et al.
Abstract: Objective: To compare oncological outcomes in women with lower uterine segment involvement (LUSI) in endometrial carcinoma (EC) stage ≥ II - staged by a minimally invasive surgery (MIS) versus laparotomy. Study design: A retrospective multi-center cohort study. Univariate analysis, Kaplan-Meier survival and Cox proportional hazard analysis were performed to compare between women staged by MIS and those staged by laparotomy. Results: Over a median follow-up period of 3 years (interquartile range, 1.5–6 years) 212 women were included, 68 (32.1%) were surgically staged by MIS. Stages of disease did not vary between MIS and laparotomy and were 32.1%, 51.9%, and 16.0%, in stages II, III and IV – respectively. Adjuvant radiation and chemotherapy rate did not differ between groups. Overall recurrence rate was comparable (p = 0.084). Locoregional recurrence rate was higher in the MIS group odds ratio 2.17, 95% confidence interval 1.19–4.20). Overall and progression free survival were similar in both groups (log rank test p = 0.08 and p = 0.912 respectively). In Cox regression model adjusting for age, comorbidities, tumor grade, stage and adjuvant therapy, route of surgery (MIS vs. laparotomy) was not associated with overall survival (p = 0.169). Conclusions: In women with advanced EC and LUSI, although MIS is associated with locoregional recurrences, survival is comparable to laparotomy.